Replication of herpes simplex virus type I DNA in permeabilized infected cells. - Jongeneel, C V (1980)
Herpes simplex type 1 (HSV)-infected Vero cells can be permeabilized by a combination of hypotonic shock and a mild emulsifier, gum arabic. Permeabilized cells will incorporate triphosphate precursors into viral and host DNA in vitro in ratios similar to those seen in vivo. This reaction is ATP-dependent and is shown to be replicative by the single strand density shift of DNA synthesized in the presence of BrdUTP. The product is heterogeneous in size, and contains a significant proportion of rapidly sedimenting forms and of unit size (55S) viral DNA. The presence of polyamines and EGTA (a specific chelator of Ca2+ ions) in the labeling medium is shown to be necessary to maintain the integrity of the replicating DNA. The average size of newly synthesized single strands, however, is smaller than seen in vivo. The reaction is sensitive to phosphonoacetic acid added at the time of labeling, at concentrations which inhibit in vivo synthesis only after one hour of pre-exposure. These properties make permeabilized cell monolayers an attractive system for the study of HSV DNA replication.